Optimization of Micro-arc Oxidation Parameters for Preparing AlN Complex Ceramic Coatings on 1060 Al Substrate. Issue 1 (January 2021) - Fan, Cuiling; Gong, Benkui; Wang, Lei; Xu, Shumin; Chen, Xiaopeng; Yang, Xiangkui; Pan, Yaokun; Feng, Rui
Abstract: In this paper, AlN complex ceramic coatings are prepared on the surface of 1060 Al by micro-arc oxidation (MAO), selecting the current density, the AlN additive amount and NaOH concentration as parameters. In order to analyze the influence of three parameters on comprehensive performance of the ceramic coating, nine models are designed via a L9 (3 3 ) orthogonal array. The surface morphology and phase composition of the MAO complex ceramic coatings are examined by scanning electron microscopy (SEM) and X-ray diffraction (XRD) respectively. Roughness, coating thickness and bonding strength of the Al substrate to the MAO complex ceramic coatings are tested and analyzed respectively. We present the results as follow: a the current density has a relatively large influence on the roughness of the coatings, the minimum roughness of the coating is 0.034 μm. b NaOH solution concentration has greater impact on the bonding strength of the coatings. The maximum critical load is 29.375 N. c AlN additive amount has the largest impact on thickness and thermal conductivity of the coatings. The biggest thickness is 15.4 μm, and the maximum thermal conductivity is 3.9436 W/(mK). The corrosion resistance of the MAO samples is obviously improved.